IOT BASED SMART AGRICULTURAL MONITORING SYSTEM - Syeda Fasiha Fatima; Dr. U. B. Shinde; Dr. Sumera Ali (International Journal of Innovations in Engineering Research and Technology, 2021)
Agriculture is one of the important sectors contributing to the Indian economy. Agriculture sector is providing the work to more than 60% people in India. With developments in electronics and the microcontroller based systems, many applications are developed by the researchers and designers to perform the agriculture operations. Internet of Things (IoT) has opened doors of opportunities to design agriculture systems with accuracy of performing task. Arduino based systems are reliable and can be used widely for agriculture applications. Authors have proposed the implementation of Arduino based IoT system for agriculture monitoring. The parameters monitored are moisture, humidity, temperature, flow etc. The hardware prototype is developed by the authors and the system is found suitable to develop for Indian agriculture sector.